Smoking and reproduction: The oviduct as a target of cigarette smoke - Riveles Karen; Talbot Prue (BMC, 2005)
Abstract The oviduct is an exquisitely designed organ that functions in picking-up ovulated oocytes, transporting gametes in opposite directions to the site of fertilization, providing a suitable environment for fertilization and early development, and transporting preimplantation embryos to the uterus. A variety of biological processes can be studied in oviducts making them an excellent model for toxicological studies. This review considers the role of the oviduct in oocyte pick-up and embryo transport and the evidence that chemicals in both mainstream and sidestream cigarette smoke impair these oviductal functions. Epidemiological data have repeatedly shown that women who smoke are at increased risk for a variety of reproductive problems, including ectopic pregnancy, delay to conception, and infertility. In vivo and in vitro studies indicate the oviduct is targeted by smoke components in a manner that could explain some of the epidemiological data. Comparisons between the toxicity of smoke from different types of cigarettes, including harm reduction cigarettes, are discussed, and the chemicals in smoke that impair oviductal functioning are reviewed.